TRANSFER AND PAYMENT APPLICATIONS SERVICE QUALITY: THE MODIFIED E-SERVQUAL AND IMPORTANCE-PERFORMANCE ANALYSIS - Moch Rizky Gumelar Erlandya; Rio Guntur Utomo; Rahmat Yasirandi (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
Innovation and technological progress have significantly impacted various sectors, notably Indonesia's financial and banking industry. This sector has seen remarkable growth, particularly with the rise of digitalization. A prominent development in this context is financial technology, or fintech, which has emerged to address needs and issues not sufficiently met by traditional banking services in Indonesia. Among fintech innovations, Transfer and Payment technologies have become increasingly popular. Despite these technologies' benefits, they are frequently criticized for various usage-related issues. This study uses the Modified E-Servqual and Importance Performance Analysis (IPA) methods to evaluate the service quality of Transfer and Payment applications in Indonesia. It aims to assess user perceptions and expectations, identify areas for improvement, and determine which service dimensions require enhancement. The research involved 400 respondents who used Transfer and Payment applications. To ensure reliability, the Kuder-Richardson (KR-21) formula is applied to the measurement tool, while descriptive analysis and IPA are utilized to evaluate and map service quality. Findings reveal that user perceptions of the Transfer and Payment applications are rated as ‘good,’ with an average score of 4.01 out of 5.00 (80%). User expectations are slightly lower, at 3.93 out of 5.00 (79%), but still categorized as ‘good.’ However, several attributes fall short of user expectations, particularly in Reliability, Personal Needs, User Friendliness, and Responsiveness.